Primary ovarian non-Hodgkin lymphoma. Case report - Reyna-Villasmil, Eduardo (2018)
Ovarian lymphomas are rare. Those presenting as a pelvic mass with initial manifestations are even rarer. Inaccurate or delayed diagnosis is often due to lesions resembling ovarian cancer and may lead to a poor outcome. We report the case of a 48-year-old female presenting with abdominal pain. Preoperative ultrasound and computed tomography showed a heterogeneous cystic mass. Laparotomy revealed a right adnexal mass of ovarian origin. Total hysterectomy, bilateral oophoro-salpingectomy, and partial omentectomy were performed. There was no evidence that the tumor had spread beyond the ovary. The diagnosis of primary non- Hodgkin lymphoma of the ovary was done by histopathological examination along with immunohistochemistry of the excised tissue. The patient received six cycles of chemotherapy. After an 18-month follow-up, the patient continues free of disease.